A new MR imaging index for differentiation of progressive supranuclear palsy-parkinsonism from Parkinson's disease. (September 2018) - Quattrone, Aldo; Morelli, Maurizio; Nigro, Salvatore; Quattrone, Andrea; Vescio, Basilio; Arabia, Gennarina; Nicoletti, Giuseppe; Nisticò, Rita; Salsone, Maria; Novellino, Fabiana; Barbagallo, Gaetano; Le Piane, Emilio; et al.
Abstract: Introduction: Differentiating clinically progressive supranuclear palsy-parkinsonism (PSP-P) from Parkinson's disease (PD) may be challenging, especially in the absence of vertical supranuclear gaze palsy (VSGP). The Magnetic Resonance Parkinsonism Index (MRPI) has been reported to accurately distinguish between PSP and PD, yet few data exist on the usefulness of this biomarker for the differentiation of PSP-P from PD. Methods: Thirty-four patients with PSP-P, 46 with PSP-Richardson's syndrome (PSP-RS), 53 with PD, and 53 controls were enrolled. New consensus criteria for the clinical diagnosis of PSP were used as the reference standard. The MRPI, and a new index termed MRPI 2.0 including the measurement of the third ventricle width (MRPI multiplied by third ventricle width/frontal horns width ratio), were calculated on T1-weighted MR images. Results: The MRPI differentiated patients with PSP-P from those with PD with sensitivity and specificity of 73.5% and 98.1%, respectively, while the MRPI 2.0 showed higher sensitivity (100%) and similar specificity (94.3%) in differentiating between these two groups. Both biomarkers showed excellent performance in differentiating PSP-P patients with VSGP from those with PD, but the MRPI 2.0 was much more accurate (95.8%) than MRPI in differentiating PSP-P patients with slowness of vertical saccades from PD patients. Conclusion: The MRPI 2.0 accurately differentiated PSP-P patients from those with PD. This new index was more powerful than MRPI in differentiating PSP patients in the early stage of the disease with slowness of vertical saccades from patients with PD, thus helping clinicians to consolidate the diagnosis based on clinical features, in vivo. Highlights: Distinguishing PSP-P from PD is challenging in the early stages of the disease. Few data exist on the usefulness of MRPI for diagnosing PSP-P patients. MRPI 2.0 is a new version of MRPI which includes the 3rd ventricular width. MRPI 2.0 accurately differentiated patients with PSP-P from those with PD. MRPI 2.0 accurately diagnosed PSP-P in the absence of vertical ocular palsy.